Focus attention and mathematical problem solving processes in students with ADHD - Nabila Ega Pramono; Sumaji; Savitri Wanabuliandari; Sekar Dwi Ardianti; Mahardika Supratiwi; Evanita (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to investigate the mathematical problem-solving abilities of students with Attention Deficit Hyperactivity Disorder (ADHD) based on their levels of focused attention. Method: This research employed a qualitative approach using a case study design conducted at SDLB Sunan Kudus, Indonesia. Three students diagnosed with ADHD were purposively selected to represent high, moderate, and low levels of focused attention. Data were collected through classroom observations, semi-structured interviews, mathematical problem-solving tests, and documentation. The problem-solving test was developed based on the National Council of Teachers of Mathematics (NCTM) problem-solving indicators and Polya’s four stages of problem solving: understanding the problem, planning a solution strategy, implementing the strategy, and reviewing the results. Data credibility was ensured through source triangulation, while the data were analysed using descriptive qualitative analysis. Findings: The results indicate that focused attention significantly influences the mathematical problem-solving processes of students with ADHD. Students with high focused attention were able to perform all stages of problem solving systematically, whereas students with moderate focused attention obtained correct answers but demonstrated incomplete procedural explanations. In contrast, students with low focused attention encountered substantial difficulties in completing the problem-solving stages effectively. Significance: These findings emphasise the importance of focused attention in supporting mathematical reasoning and provide insights for educators in designing instructional strategies that strengthen attention regulation and structured problem-solving skills for students with ADHD.